In-vitro Comparative Study to Evaluate Fracture Strength for PMMA CAD/CAM discs (indirect technique) and Bis-acrylic resin (direct technique) Used in the Fabrication of Provisional Bridges. (Journal of Hama University, 2022)
AbstractInterim (temporary) restorations play an important role in the prosthodontic treatment plans, and these temporary restorations serve from the beginning of the preparation phase until its end when the permanent fixed restoration is cemented and fixed.Due to the importance of these prostheses, several studies have been carried out aimed at knowing the optimal material for the manufacture of these interim prostheses. Poly methyl methacrylate resins (PMMA) and Composite-based resins (CBR) are the most common materials used in the fabrication of these interim fixed prostheses. Moreover, the breakage of those interim prostheses is considered to be the most important reason for its clinical failure; therefore, knowing the mechanical properties of the dental materials used in the fabrication of these prostheses is important and should not be neglected, to ensure the clinical success as much as possible.Aim of the research: This research aims to compare and evaluate the fracture resistance of both polymethyl methacrylate PMMA (indirect method, using CAD/CAM technology), and bis-acrylic resin (direct method), which are used in the manufacture of temporary bridges that replace the missing lower first molar.Materials and methods: The research sample consisted of /20 / interim bridges, which were fabricated on a metal master typodont (dentiform), made from Cr-Co alloy, to stimulate the average dimension of the prepared second premolar and the second molar, within the first molar as a missing tooth. Then the sample was divided into two identical groups as follows:The first group: the interim restorations were made by the indirect method (PMMA CAD/CAM prefabricated disks). While the second group’s restorations were made by the direct method (bis-acrylic resin). After that, all groups were subjected to fracture resistance mechanical test, then collected data was analyzed.Results: the average fracture resistance of the PMMA CAD/CAM interim bridges (indirect technique), was higher than the average fracture resistance of the bis-acrylic resin (direct technique).
Keywords: provisional restoration; interim restoration; PMMA; CAD/CAM; fracture resistance; bis-acrylic resin